2017
DOI: 10.1111/jgs.15124
|View full text |Cite
|
Sign up to set email alerts
|

Can a Left Ventricular Assist Device in Individuals with Advanced Systolic Heart Failure Improve or Reverse Frailty?

Abstract: Background/Objectives Frailty, characterized by decreased physiologic reserves, is strongly associated with vulnerability to adverse outcomes. Features of frailty overlap with those of advanced heart failure (HF), making a distinction between these phenotypes difficult. We sought to determine if implantation of a left ventricular assist device (LVAD) would improve the frailty phenotype. Design Prospective, cohort study Setting Five academic medical centers. Participants 29 frail subjects (age 70.6±5.5 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 56 publications
0
55
0
4
Order By: Relevance
“…20 Jha and colleagues demonstrated that one-third of their heart failure population was identified as being frail and was independent of age, sex, or ejection fraction. 73,74 Notably, the heart group did not feel that rehabilitation alone was a viable therapeutic option for patients as improvement in frailty would be minimal and would expose patients to a heightened risk of death. Further, nonfrail patients who went on to receive a heart transplant had a 1-year posttransplant survival of 100%, compared to 52% in frail patients.…”
Section: Frailty Considerations In Heart Transplantationmentioning
confidence: 99%
See 1 more Smart Citation
“…20 Jha and colleagues demonstrated that one-third of their heart failure population was identified as being frail and was independent of age, sex, or ejection fraction. 73,74 Notably, the heart group did not feel that rehabilitation alone was a viable therapeutic option for patients as improvement in frailty would be minimal and would expose patients to a heightened risk of death. Further, nonfrail patients who went on to receive a heart transplant had a 1-year posttransplant survival of 100%, compared to 52% in frail patients.…”
Section: Frailty Considerations In Heart Transplantationmentioning
confidence: 99%
“…The placement of an MCSD (to aid rehabilitation) in advanced heart failure patients suggests that approximately 50% of the patients have an improvement in their frailty level, but importantly, the majority of patients would still be considered prefrail. 73,74 Notably, the heart group did not feel that rehabilitation alone was a viable therapeutic option for patients as improvement in frailty would be minimal and would expose patients…”
Section: Frailty Considerations In Heart Transplantationmentioning
confidence: 99%
“…In patients undergoing DT-LVAD, there was a more than threefold increased risk of death in patients in the highest frailty tertile [85]. In approximately half of older adults with AdHF who were frail before LVAD implantation, frailty had decreased 6 months after implantation [98]. Fitness-associated biological age seems a more robust determinant of outcomes than CA [99].…”
Section: Frailty and Outcomesmentioning
confidence: 97%
“…In advanced HF patients undergoing LVAD implantation or heart transplantation, preoperative frailty assessment can indicate those with increased postoperative risks of death, prolonged utilization of intensive care unit and length of hospital stay (Jha et al, 2016 , 2017 ). Importantly, frailty can reverse or be improved in some patients with HF (Lee et al, 2014 ; Jha et al, 2016 ; Maurer et al, 2017 ), refuting the notion that frailty is permanent, inevitably irreversible and age-dependent.…”
Section: Epidemiologymentioning
confidence: 99%
“…In patients with chronic HF, multidisciplinary interventions including strength and muscle training, physical rehabilitation, and nutritional supplementation may improve functional impairment and deficits (Piepoli et al, 2004 ; O'Connor et al, 2009 ; Davies et al, 2010 ; Rozentryt et al, 2010 ; Avni et al, 2012 ; Gotsman et al, 2012 ; Taylor et al, 2014 ). Furthermore, in eligible candidates frailty may be reversible with left ventricular assist device (LVAD) therapy or heart transplant (Jha et al, 2016 , 2017 ; Maurer et al, 2017 ). However, these advanced therapies are costly and may not be available or suitable for many patients with HF.…”
Section: Introductionmentioning
confidence: 99%